Engineering anti-thrombogenic and anti-infective catheters through a stepwise metal-catechol-(amine) surface engineering strategy - Siyuan Yue; Wentai Zhang; Qing Ma; Zhen Zhang; Jing Lu; Zhilu Yang (Bioactive Materials)
Thrombosis and infection are pivotal clinical complications associated with interventional blood-contacting devices, leading to significant morbidity and mortality. To address these issues, we present a stepwise metal-catechol-(amine) (MCA) surface engineering strategy that efficiently integrates therapeutic nitric oxide (NO) gas and antibacterial peptide (ABP) onto catheters, ensuring balanced anti-thrombotic and anti-infective properties. First, copper ions were controllably incorporated with norepinephrine and hexanediamine through a one-step molecular/ion co-assembly process, creating a NO-generating and amine-rich MCA surface coating. Subsequently, azide-polyethylene glycol 4-N-hydroxysuccinimidyl and dibenzylcyclooctyne modified ABP were sequentially immobilized on the surface via amide coupling and bioorthogonal click chemistry, ensuring the dense grafting of ABP while maintaining the catalytic efficacy for NO. This efficient integration of ABP and NO-generating ability on the catheter surface provides potent antibacterial properties and ability to resist adhesion and activation of platelets, thus synergistically preventing infection and thrombosis. We anticipate that this synergistic modification strategy will offer an effective solution for advancing surface engineering and enhancing the clinical performance of biomedical devices.